Morphological matching and phenological overlap promote niche partitioning and shape a mutualistic plant–hawkmoth network - Lautenschleger, Andreza; Vizentin‐Bugoni, Jeferson; Cavalheiro, Lis B.; Iserhard, Cristiano A. (Ecological entomology, 2021)
1. Species interact with one another in communities forming complex interaction networks which are shaped by multiple non‐exclusive processes. Although plant–hawkmoth interactions have been studied for over a century, how processes underlying species' specialisation influence community‐level patterns of niche partitioning and contribute to the emergence of network structures remains poorly investigated. 2. This study described a mutualistic plant–hawkmoth network sampled for 18 consecutive months in Southern Brazil and tested (i) whether it presents modular and/or nested structures and (ii) what drivers (morphologies, phenologies, or abundances) are more important in defining interaction intensities. 3. Network structure was modular, presenting three distinct modules, and had a nestedness value lower than null model expectations. Interaction frequencies were primarily defined by morphological matching and phenological overlap but were not importantly influenced by species' relative abundances. Module composition reinforced the importance of morphological matching, as well as barriers imposed by morphology, and also suggested that modularity may be a consequence of other factors, such as timing between hawkmoth flight period and plants' anthesis. 4. This study's data contribute to filling the shortage of plant‐centred interaction networks involving hawkmoths and plants and reveal that modularity emerges likely as a consequence of processes thought to shape niche partitioning in this system, as well as in other pollination networks. The findings of this study are in agreement with the neutral‐niche continuum model, which predicts that, in systems with high trait functional variation (morphologies and phenologies in this case), niche‐based processes such as trait matching must be relatively more important than abundances as drivers of interspecific interactions. Plant‐hawkmoth interactions network presented modular structure, reflecting niche partitioning primarily related to morphological matching and barriers imposed by phenology and morphology.Interaction frequencies were mainly defined by morphological matching and phenological overlap, but were not importantly influenced by species' relative abundances.Our findings agree with the ‘neutral‐niche continuum model’ which predicts that in systems with high functional variation, niche‐based processes must be relatively more important than neutrality as drivers of interactions.